Long-term remission of metastatic pleomorphic paratesticular rhabdomyosarcoma with chemotherapy in an adolescent boy - A case report - Intezar Mehdi; Shashi Ranjani; Shivakumar Swamy; K Venkatachala (Indian Journal of Medical and Paediatric Oncology)
Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in the pediatric age group. They are classified based on the histopathological characteristics. The prognosis of RMS depends on the site of occurrence and the histopathology. Although paratesticular site is considered as one of the favorable sites, pleomorphic histology, even at this favorable site, confers a poor prognosis. Treatment includes surgery chemotherapy and radiation in metastatic cases. Here, we describe a case of an adolescent boy with pleomorphic paratesticular RMS treated successfully with chemotherapy.